INFLUENCE OF THE SEPAJ METHOD ON THE QUALITY OF PINK WINE SAMPLES - Konul Fikret Imanova; Teymur Musa Musayev (International Journal of Innovative Technologies in Social Science, 2023)
Quality composition of pink wine samples made from sepaj of grape harvest obtained from Madrasa and Bayanshira varieties was analyzed. Sepaj 80:20; 60:40; 40:60; 20:80 obtained from mixing red grapes with white grapes in proportion. Samples of pink wine “Al wine” made from Tavkveri grape variety were in a superior position in terms of composition and organoleptic quality. Among the samples, the 60:40 sepaj sample was rated higher for the optimality and organoleptic quality of the composition indicators. So, it differed from other analogs in that it was 0.3-0.5 points ahead.